Expert reviewsRadial artery occlusion after percutaneous coronary interventions – an underestimated issue - Sławin, Janusz; Kubler, Piotr; Szczepański, Andrzej; Piątek, Joanna; Stępkowski, Michał; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
The femoral approach is the most common arterial access for percutaneous coronary artery interventions. Despite the convenience and simplicity of this approach, it is burdened with a high risk of arterial puncture bleeding, which worsens the prognosis of the patient. An alternative approach through the radial artery has been gaining more and more popularity in recent years. This is due to a significant reduction of local bleeding complications as compared with the femoral artery approach. The use of the radial approach in patients with ST-segment elevation myocardial infarction improves outcome, reducing the risk of death, subsequent myocardial infarction and stroke, and is the preferred approach according to the latest ESC guidelines. In addition to improving safety, it is beneficial for improving patient comfort, with a shorter recovery after the procedure, shorter hospitalization and lower medical costs. One of the major complications of procedures performed through the radial approach is radial artery occlusion (RAO). Although it usually has an asymptomatic course, RAO eliminates the ability to use the radial artery as an access in the future. A number of factors that contribute to the occurrence of RAO have been identified, such as the size of the sheath and the catheter, diameter ratio of the sheath to the diameter of the radial artery, insufficient anticoagulation and, above all, the way of obtaining hemostasis at the puncture site: the duration of artery compression after sheath removal and the preservation of artery patency during compression (so-called patent hemostasis). This paper presents the current state of the art about the factors that contribute to the occurrence of RAO and methods for preventing this complication.